If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 16 = 86 Reorder the terms: 16 + 10x = 86 Solving 16 + 10x = 86 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 10x = 86 + -16 Combine like terms: 16 + -16 = 0 0 + 10x = 86 + -16 10x = 86 + -16 Combine like terms: 86 + -16 = 70 10x = 70 Divide each side by '10'. x = 7 Simplifying x = 7
| 3x+16=37 | | (10n)7= | | 8-(2x+1)-8+3=3-(3x+3) | | 98-9x=4x+7 | | 3.1+(8.6+m)= | | P=5h+5u | | ((x^2-9)/(x^2+7x+12))/((x^2-4x-32)/(x^2-3x)) | | -4n+18=-2n-18 | | 8x+b+4x= | | 1-3.5t=1.4-2.33t+1.5 | | 3f+4k-5f= | | -5=5t+5 | | 8x^4+35x^2+12=0 | | P=10 | | 0=-5p(-3q)+(4m)(-6n) | | 2/3x+4=-26 | | 10x+27=6+17x | | 2(X+7Y)= | | 5t+5(t+3)=195 | | 8z-51z+15-30z-15z+2z=53z+15+31z+2z-172 | | -10x-7x=10x+24 | | 5x-13x= | | -4.9t^2+179t+12.4=0 | | (1/3)9s | | 5/5*1/2 | | 20*x-3*y= | | 37+x=2(8+x) | | 5(t-3)+7t=6(2t+5)-8 | | 39=6x+3 | | -5+8=m-4 | | p=6x+3 | | 15t+(4-t)10=50 |